PT Petrokimia Care Sharing CSR Program: Society Potential Empowerment to Improve The Society Life Quality at Roomo Village and Karangturi Sub-District Gresik - Richa Meyta Sari; Dewi Khrisna Sawitri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The community empowerment program in Roomo Village and Karangturi Village is a part of the Social and Environmental Responsibility (SER) program carried out by PT Petrokimia Gresik and implemented in 2023. The Corporate Social Responsibility (CSR) program carried out consists of distributing basic necessities and training to Micro, Small and Medium Enterprises around the company. This community development program is included in the community relations category whose programs tend to take the forms of corporate generosity or charity. With the existence of Social and Environmental Responsibility (SER) through the provision of basic necessities, community empowerment is expected to improve the quality of life for people in Roomo Village and Karangturi Village